2010
DOI: 10.1080/1072303x.2010.492003
|View full text |Cite
|
Sign up to set email alerts
|

Examining Change Within Interlibrary Loan

Abstract: Technological innovations have changed the interlibrary loan landscape, leading many of its practitioners to wonder what the future holds for interlibrary loan. Examining the way in which change is discussed can reveal some insecurities on the part of interlibrary loan workers and can also provide direction as to where interlibrary loan is going.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The common conclusions include the importance of speed and convenience, and preference for desktop access (Connaway and Dickey, 2010). McHone-Chase (2010) presents a historical perspective through a review of literature from 1995 to 2009 on how technology has changed user expectations and driven change in ILL. She found ILL has been extensively affected by technology and is struggling to keep up with user expectations for service. ILL requests are increasing due to a combination of libraries purchasing less, and users' ability to find more content through databases.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The common conclusions include the importance of speed and convenience, and preference for desktop access (Connaway and Dickey, 2010). McHone-Chase (2010) presents a historical perspective through a review of literature from 1995 to 2009 on how technology has changed user expectations and driven change in ILL. She found ILL has been extensively affected by technology and is struggling to keep up with user expectations for service. ILL requests are increasing due to a combination of libraries purchasing less, and users' ability to find more content through databases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study notes some common conclusions about changed user behavior, including the importance of speed and convenience, and preference for desktop access to scholarly content (OCLC Research, 2010). McHone-Chase (McHone-Chase, 2010) presents a historical perspective through a review of literature from 1995 to 2009, on how technology has changed user expectations and driven change in interlibrary loan. She found ILL has been extensively affected by technology and is struggling to keep up with user expectations for service.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning the evolution of ILL services, she writes that the transition from a "negative service" to an "essential function" is because "of the amplified importance that libraries have placed on the model of access over ownership" (p. 202). She synthesizes various perspectives on the issue, one of which suggests that ILL's role will move from a public service in processing and providing requested items to perhaps a more collection development focused role, as monitors of what materials are being used at any given time (p. 203) (McHone-Chase, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, changes in scholarly publishing, information discovery, and library service models have the potential to influence the pattern of requests handled by ILL departments. Over the past two decades, libraries have adapted to numerous scenarios that had the potential to dramatically alter ILL workflow, including the transition from print to electronic resources, massive journal cancellations in response to budget constraints, the implementation of discovery systems, and the adoption of pay-perview (PPV) services [1,2]. Despite concerns that these changes would have major repercussions for ILL departments, a review of the literature indicated that these fears did not materialize.…”
Section: Introductionmentioning
confidence: 99%